Students' perception towards a career in the homestay industry in Sabah - Ku Intan Putra Ku Husin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The homestay industry nowadays is seen growing rapidly and it is considered as a branch of entrepreneurial career and a profitable source of income. As a career in entrepreneurship requires a high level of skill compared to a salary job, so there are various perceptions about the challenges of entrepreneurship. Therefore, this study was conducted to see how far the students’ perception towards a career in the homestay industry. The research instrument used is a questionnaire that has been distributed to Tawau Polytechnic diploma students. The sampling technique used is random sampling. The data obtained was analyzed descriptively using SPSS v.23 (Statistical Package for the Social Sciences) software. A total of 55 have answered the questionnaire. The findings of the study analysis show that most respondents agree with the study items. Therefore, the findings of the study explain that many respondents have a positive perception of a career in the homestay industry and consider this industry interesting However, even though they have a positive perception in the homestay field, many respondents are not sure if they have the desire to build a career in the homestay business. The implications of this study explain the need for exposure related to the ins and outs of the homestay business from the homestay entrepreneurs themselves so that students understand that there is a wide opportunity and potential for the homestay industry in Sabah.